2011
DOI: 10.1186/1476-072x-10-65
|View full text |Cite
|
Sign up to set email alerts
|

Studying relationships between environment and malaria incidence in Camopi (French Guiana) through the objective selection of buffer-based landscape characterisations

Abstract: BackgroundMalaria remains a major health problem in French Guiana, with a mean of 3800 cases each year. A previous study in Camopi, an Amerindian village on the Oyapock River, highlighted the major contribution of environmental features to the incidence of malaria attacks. We propose a method for the objective selection of the best multivariate peridomestic landscape characterisation that maximises the chances of identifying relationships between environmental features and malaria incidence, statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…As in Stefani et al [46], the assumption is also made that the transmission is domiciliary, making it possible to link incidence rates to the dwellings and the environment features surrounding them; due to the small magnitude of the study area (15 km 2 ), the spatial disparity of the incidence rates cannot be explained by climatic and/or major environmental disparities in space; finally, the children in the cohort share similar immunity levels and genetic susceptibility to malaria transmission [10]. However, according to Stefani et al [10], the number of inhabitants in the home, the use of tropical repellents and domestic insecticides, the interventions of the county mosquito control services, and going to bed before 7:00 pm are protective factors against malaria transmission and can partially explain incidence rate disparities.…”
Section: Quantitative Evaluationmentioning
confidence: 53%
See 3 more Smart Citations
“…As in Stefani et al [46], the assumption is also made that the transmission is domiciliary, making it possible to link incidence rates to the dwellings and the environment features surrounding them; due to the small magnitude of the study area (15 km 2 ), the spatial disparity of the incidence rates cannot be explained by climatic and/or major environmental disparities in space; finally, the children in the cohort share similar immunity levels and genetic susceptibility to malaria transmission [10]. However, according to Stefani et al [10], the number of inhabitants in the home, the use of tropical repellents and domestic insecticides, the interventions of the county mosquito control services, and going to bed before 7:00 pm are protective factors against malaria transmission and can partially explain incidence rate disparities.…”
Section: Quantitative Evaluationmentioning
confidence: 53%
“…While a discoidal window intuitively seems the most appropriate, the choice of the disk radius is not trivial. Stefani et al used a data-driven selection for the optimal radius of the discoïdal window to explain the malaria incidence rates in the village of Camopi, and concluded that the optimal radius was 400 m for the P. falciparum and 100 m for the P.vivax incidence rates [46]. However, it was shown that P. vivax incidence was poorly correlated to the landscape features in comparison with P. falciparum incidence, suggesting that the P. vivax relapses were not correctly identified [46].…”
Section: Circle_am Contig_mn and Contig_ammentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmodium falciparum, is known to be the plasmodium species that causes almost all the cases of malaria in Ghana (3) . The incidence of Plasmodium falciparum seems to be linked to environmental factors (4) . Sites for mosquitoes (the vectors for malaria parasites) to breed include ditches, vegetation, and rainfall (5,6) which abounds in Ghana.…”
Section: Introductionmentioning
confidence: 99%